2020
DOI: 10.36937/ben.2020.003.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microcrack Healing Techniques on Tensile Strength of Asphalt

Abstract: Asphalt concrete pavement practices repeated loading and environmental impacts and suffers distresses. Microcracks usually occurs at early stage of pavement life while the pavement can heal itself under controlled conditions. Microcrack healing process can be controlled and accelerated using various techniques. In this investigation, iron filling was implemented as partial substitute of sand to support the healing process while both induction and external heating techniques were adopted to control the healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The increase in the Marshall stability value of the mixture is due to adding of plastic particles to the mixture which cause a decrease in the viscosity of the mixture. Similar results were reported by Sarsam & Al Tuwayyij [8]. In Figure 9, the optimal asphalt content (OAC) for each mixture containing a certain percent of plastic particles was computed by taking the average values of asphalt contents at maximum unit weight, maximum stability, and asphalt median air void ratio.…”
Section: Volumetric Propertiessupporting
confidence: 55%
See 1 more Smart Citation
“…The increase in the Marshall stability value of the mixture is due to adding of plastic particles to the mixture which cause a decrease in the viscosity of the mixture. Similar results were reported by Sarsam & Al Tuwayyij [8]. In Figure 9, the optimal asphalt content (OAC) for each mixture containing a certain percent of plastic particles was computed by taking the average values of asphalt contents at maximum unit weight, maximum stability, and asphalt median air void ratio.…”
Section: Volumetric Propertiessupporting
confidence: 55%
“…The material was added in different proportions to study the mechanical properties and RM of asphalt. It was found that 5% yields the best results by improving asphalt concrete sample stability and flow values, as well as showing the highest RM value [7,8]. An investigation of developing asphalt properties by incorporating plastic waste for road pavement construction was conducted.…”
Section: Introductionmentioning
confidence: 99%